Deconstruction of Mrs. Driver’s Character in Mary Norton’s the Borrowers Novel - Mawar, Suci Sri; Sudirman, Eka Pratiwi (B-CRETA Publisher (CV. Borneo Citra Kreatama), 2024)
This research is concerned with the deconstruction of Mrs. Driver’s character in Mary Norton’s The Borrowers novel. This research aimed to describe the meaning of her character and deconstruct her previous fixed view using the determined binary oppositions. This research used Derrida’s deconstruction with a qualitative design in the form of a description. The data in this research were dialogues, text, narration, sentences related to Mrs. Driver's character and obtained by reading the novel several times. In the analysis, the depiction of Mrs. Driver’s character and characterization in the novel is described using Robert's theory which is the action of characters reveal their qualities, what characters say reveals what they are like, what others say tells us about a character and the author, speaking as a storyteller or an observer may present judgments about characters. Then, her character is deconstructed using the determined binary oppositions, they are: offensive vs. defensive, bad person vs. good person, and powerful vs. powerless. The researcher deconstructed Mrs. Driver's character and discovered her previously fixed views as someone offensive, bad, and powerful are not absolute. The researcher concluded that Mrs. Driver's character inherited not just a bad meaning but also a good trait. Thus, the meaning of her character is undecidable. This research emphasized that literary works never have a fixed meaning, so the reader should not be chained by only one perspective.